The Usefulness of Neurobehavioral Task as Driver’s Fatigue Detection Technology - Herman Rahadian Soetisna; Ida Ayu Putu Mahadewi; Annas Fatkhurrohman; Gradiyan Budi Pratama; Hardianto Iridiastadi (Perhimpunan Ergonomi Indonesia, 2020)
Fatigue is a significant contributor to motor-vehicle accidents and fatalities. The purpose of this study was to evaluate the use of neurobehavioral task (i.e. Psychomotor Vigilance Task (PVT) and Stroop Test) as fatigue detection technology of motor-vehicle drivers. Twelve male participants (M ± SD; 35.58 ± 3.58 years) were asked to drive 6-hour long into 2 trip (Bandung – Bekasi and Bekasi – Bandung). Results showed that neurobehavioral task may be useful to detect the fatigue of motor vehicle’s driver, specifically using this three parameters, i.e. PVT-M, #L, and RTCA. Mental fatigue score from SOFI had a significant correlation with those parameters. Regular check for drivers (i.e. before, during, and after the duty) using neurobehavioral task may improve the impact of FRMS implementation in Indonesia. Furthermore, PVT, as the gold standard of application using this approach, may be replaced by a shorter test, such as Stroop Test.